Photonics: Making light work for us - Simpson, Cather; Erkintalo, Miro; Oosterbeek, Reece; Ashforth, Simon; Broderick, Neil; Coen, Stéphane; Murdoc, Stuart; Harvey, John (New Zealand Science Review, 2015)
Photonics is the science and technology of creating, controlling and using light. Like electronics in the 20th Century, photonics is the enabling technology of the 21st Century. It underpins the solutions to many of the world’s current challenges, including high-speed communications, clean energy, advanced manufacturing, healthy ageing, and global climate change. The photonics industry is growing at a rapid pace, much faster than global GDP, with a global market size of over 600 billion euro predicted by 2020 (1). Truly, we are putting light to work for us to make the world a better place.